Digital Transformation: Improving Operation Efficiencies Through AI-Predictive Analysis Network at a Vancouver Catering Services - Innocent Mafiele; Rustam Nigmatullin; Farzaneh Tajikfilestan; Gaurav Pawar; Anu Chawla (International Journal of Management and Data Analytics)
An enormous global food firm is growing quickly and getting ready to move to a new location, but it needs more software infrastructure and antiquated technologies, which present serious problems. This paper suggests a thorough digital transformation plan to overcome these obstacles and facilitate the company's growth. The concept is centred on deploying the AI-driven Predictive Analytics Network (APAN), a technological solution intended to boost productivity overall, streamline workflows, and improve the efficiency of food delivery. APAN seeks to solve inefficiencies from the company's expanded scale and staff by automating repetitive tasks and optimizing essential business processes. The company's technological infrastructure will be modernized, employee collaboration and communication will increase, customer service will be improved, and operating expenses will be decreased with the proposed digital transformation. This idea is valuable since it can help the business expand, enhance customer satisfaction, and guarantee more economical and efficient operations. Employees, clients, and business partners will all profit from this change, which will ultimately create an organizational culture that is more creative and effective.